Pengembangan Model Pembelajaran Blended Learning Pada Program Diklat Pelaut Berbasis Kebutuhan Industri - Pambudi Widiatmaka; Rufiajid Navy Abritia; Indah Nurhidayati (LPPM AKMI SUAKA BAHARI CIREBON, 2023)
Politeknik Ilmu Pelayaran Semarang has one of the trainings for seafarers, ATT II training. The current education model is still considered not to provide optimal competence, so competency improvement is needed. This research was conducted by analyzing and discussing the current learning model with various parties. This study emphasizes a combination of learning after student officers have received the material face-to-face and in the laboratory. It is necessary to carry out learning using blended learning so that it is expected to improve practical competence. This research was conducted using research and development methods. The stages of the model made are factual models, theoretical models, hypothetical models, model trials, and final models. The research results on the factual model show that several aspects can still be improvised, namely in planning, organization, implementation, and monitoring (evaluation). Based on the development of existing theories, a blended learning model is compiled that can provide an innovative and valuable learning experience for students. Blended learning combined with experiential learning in the field, known as fieldwork programs, will encourage competencies and skills, especially psychomotor aspects. The trial test results show a significant difference with a sig value of 0.000, the initial group value was 79.71, and the final group was 85.10. The final model tested and validated by experts shows that blended learning can improve students' competence.